Volatile organic compounds enhancing sulfuric acid-based ternary homogeneous nucleation: The important role of synergistic effect. (15th July 2020) - Zhao, Yu; Liu, Yi-Rong; Jiang, Shuai; Huang, Teng; Wang, Zi-Hang; Xu, Cai-Xin; Feng, Ya-Juan; Huang, Wei
Abstract: New particle formation (NPF) is an important source of atmospheric aerosols. Sulfuric acid (SA) and water (W) are recognized as essential participating substances in the nucleation of the atmosphere. In addition, as one of the most common organic acids, oxalic acid (OA) can improve NPF when amine such as methylamine (MA) is present. However, exploring the properties of atmospheric particles made up of different components is challenging and the role of volatile organic compounds in SA–based ternary homogeneous nucleation is still lacking in research. In this work, the structures and energies of (SA)x (OA)y (MA)z (W)m (0 ≤ x, y, z ≤ 3, 0 ≤ m ≤ 1) are investigated. The results indicate that it is accessible for SA to form clusters with OA and MA molecules through hydrogen bonds and proton transfer interactions. The analysis of non–covalent interactions and proton transfer reveals that ternary nucleation systems have stronger hydrogen bonds and more proton transfers than binary systems to stabilize the clusters. In terms of the thermodynamic properties, the Gibbs free energies of the clusters will decrease as the addition of SA, OA or MA molecules indicating that the synergistic effect of these three substances may be of potential in forming the initial cluster and subsequent growth processes. Moreover, the evaporation rates of clusters show that the synergistic effect of ternary clusters leads to a decrease in evaporation rate which may promote atmospheric nucleation. Highlights: Nucleation capability of ternary system is stronger than that of binary system. Ternary clusters are more stable than binary clusters due to synergistic effect. Synergistic effect reduces evaporation and stabilizes pre-nucleation clusters.